A simulation study on the conversion efficiency of catalytically active particulate filters. (31st July 2016) - Opitz, B.; Votsmeier, M.
Abstract: A catalytically active particulate filter with a first order catalytic reaction taking place inside the filter walls is investigated by numerical simulation. The conversion efficiency for different channel geometries and operating conditions is systematically studied as a function of the governing dimensionless parameters. It is found that the conversion efficiency of a catalytically coated wall flow filter is very close to that of an ideal plug flow reactor over the full range of realistic operating conditions. Only in a range of intermediate residence times, the filter reactor shows some diffusion limitation which leads to conversion efficiencies slightly below that of the plug flow reactor. In all cases, these deviations from ideal conversion behaviour are below 15%. If the filter and the open monolith are compared at identical operating conditions and channel geometries, for fast reactions, the filter reactor shows higher conversion efficiency than the open monolith, since in this case the open monolith becomes strongly mass transfer limited. However, there can be a small range of conditions where the monolith is slightly more efficient than the filter. The reason for this effect is that due to the thinner washcoat layer the onset of mass transfer limitation in the coated monolith is shifted to higher reaction rates, compared to the filter reactor. Highlights: Conversion efficiency of catalyzed particulate filters was studied. Conversion studied as function of the governing dimensionless parameters. Conversion efficiency of catalysed filter is very close to ideal plug flow reactor. Systematic comparison of filter reactor and conventional open monolith.